2016
DOI: 10.1111/jbi.12783
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Australia's temperate marine phylogeography, with new evidence from high‐dispersal gastropods

Abstract: Aim We provide an overview of the location and ages of coastal phylogeographical breaks in southern Australian planktonic dispersers, and test the hypothesis that the absence of such breaks in some species is an artefact of insufficient resolution of genetic markers when such breaks evolved comparatively recently. Location Temperate coastal Australia. Methods We generated a large (> 1500 individuals) data set from rapidly evolving microsatellite markers for two codistributed Australian coastal gastropods, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 104 publications
(139 reference statements)
2
37
0
Order By: Relevance
“…It has been proposed that greenlip abalone metapopulation structure varies among biogeographic regions and that data on life history and recruitment dynamics are needed for guiding regional sustainable management (Miller et al., ). This agrees with seascape genetic studies spanning the entire southern Australian coast which show that metapopulation connectivity and recruitment success in broadcast spawning intertidal organisms vary along the coast in part due to differences in on‐shelf oceanographic dynamics (Teske et al., , ). The genomewide signal consistent with stepping‐stone dispersal detected in our study emphasizes the importance of management policies aimed at maintaining demographically secure local subpopulations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It has been proposed that greenlip abalone metapopulation structure varies among biogeographic regions and that data on life history and recruitment dynamics are needed for guiding regional sustainable management (Miller et al., ). This agrees with seascape genetic studies spanning the entire southern Australian coast which show that metapopulation connectivity and recruitment success in broadcast spawning intertidal organisms vary along the coast in part due to differences in on‐shelf oceanographic dynamics (Teske et al., , ). The genomewide signal consistent with stepping‐stone dispersal detected in our study emphasizes the importance of management policies aimed at maintaining demographically secure local subpopulations.…”
Section: Discussionsupporting
confidence: 87%
“…For southwestern Australia, if we consider only the periods relevant for the spawning and pelagic larval duration of greenlip abalone (Prince, Sellers, Ford, & Talbot, ; Shepherd, Lowe, & Partington, ), advection connectivity simulations suggest that >80% of larvae released along our study region will reach the boundary currents responsible for long‐distance transport (see supplementary material in Teske et al., ). Indeed, population genetic studies of intertidal organisms with contrasting life histories (e.g., kelps and snails) have shown that strong oceanographic currents along this coastal region can promote eastward dispersal from Cape Leeuwin towards the Great Australian Bight (Coleman, Feng, Roughan, Cetina‐Heredia, & Connell, ; Teske et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…, Colgan , Teske et al. ) and around the Florida peninsula (e.g., algae, fishes, marine invertebrates, a coastal bird, and a coastal vascular plant species phylogeographic concordance; Gurgel et al. , Soltis et al.…”
Section: Discussionmentioning
confidence: 99%
“…When sea levels fell to lower than 50 m below contemporary levels, a land bridge formed between Victoria and Tasmania in the present day area of Bass Strait. The emergence and subsequent submergence of the Tasmanian land bridge would have cut off circulation and gene flow between the Southern Ocean and the Tasman Sea, providing opportunities for reproductive isolation in refugia (Sinclair et al., ), differentiation via diversifying selection, and lineage extinctions (Teske, Sandoval‐Castillo, Waters, & Beheregaray, ). Several other species show strong genetic breaks or phylogenetic structure at this point (Ayre et al., ; Dawson, ; Sherman et al., ; Waters, ; Waters & Roy, ; York, Blacket, & Appleton, ).…”
Section: Discussionmentioning
confidence: 99%